Research the behaviour and properties of WWER type fuel claddings from Zr1%Nb alloy in loss of the coolant accident - Semerak, M.M.; Lys, S.S. (Вопросы атомной науки и техники, 2021)
The paper presents safety criteria placed on fuel rod condition in loss of the coolant accident (LOCA) conditions as applied to reactor plants with WWER. The paper reveals briefly experimental studies carried out to validate safety criteria (acceptance criteria). The scope of the data experimentally obtained by research the behaviour and properties of WWER type fuel claddings from Zr1%Nb alloy under loading conditions simulating the stage of core flooding with water in LOCA suffices to judge the character and numerical value of criterional parameters of the embrittlement criterion in terms of the cladding stability upon flooding and subsequent implementation of fuel assembly (FA) unloading and transportation. Accidents are considered involving loss of coolant by primary circuit which are characterized by conditions of degraded heat transfer from fuels. During accidents loss of tightness by fuel rod cladding is tolerable, however, in this case, the cooling of a distorted fuel rod and the dismantling (unloading) of the core after an accident have to be feasible. Наведено критерії безпеки, що пред’являються до стану твелів в умовах проектних аварій з втратою теплоносія для реакторних установок з ВВЕР. Представлений короткий огляд експериментальних досліджень, проведених з метою обґрунтування критеріїв безпеки. Обсяг експериментальних даних, отриманих при дослідженні поведінки і властивостей оболонок твелів реактора типу ВВЕР зі сплаву Zr1%Nb в умовах навантаження, імітуючих стадію затоплення активної зони водою при аварії з втратою теплоносія, достатній для судження про характер і чисельне значення критеріальних параметрів окрихчування з точки зору стійкості оболонок під час заливу і видаленні ТВЗ та транспортуванні. Розглядаються аварії з втратою теплоносія першого контуру, для яких характерне погіршення умов тепловідведення від твелів. У процесі аварій допустима розгерметизація оболонки твела, однак при цьому повинна зберігатися можливість охолодження твела зі зміненою геометрією і можливість розбирання (вивантаження) активної зони після аварії. Приведены критерии безопасности, предъявляемые к состоянию твэлов в условиях проектных аварий с потерей теплоносителя для реакторных установок с ВВЭР. Представлен краткий обзор экспериментальных исследований, проведенных с целью обоснования критериев безопасности. Объем экспериментальных данных, полученных при исследовании поведения и свойств оболочек твэлов реактора типа ВВЭР из сплава Zr1%Nb в условиях нагружения, имитирующих стадию залива активной зоны водой при аварии с потерей теплоносителя, достаточен для суждения о характере и численном значении критериальных параметров охрупчивания с точки зрения стойкости оболочек при заливе и извлечении ТВС и транспортировке. Рассматриваются аварии с потерей теплоносителя первого контура, для которых характерно ухудшение условий теплоотвода от твэлов. В процессе аварий допустима разгерметизация оболочки твэла, однако при этом должны сохраняться возможности охлаждения твэла с измененной геометрией и разборки (выгрузки) активной зоны после аварии.